Governance as a Global Development Goal? Setting, Measuring and Monitoring the Post‐2015 Development Agenda. Issue 2 (2nd November 2014) - Hulme, David; Savoia, Antonio; Sen, Kunal
Abstract: The increasing realisation that governance quality is a fundamental element of long‐run development has led to its consideration as a desirable development goal in its own right. To contribute to such a process, this article provides a framework to set, measure and monitor governance goals in the post‐2015 development agenda. First, we assess whether existing cross‐national measures on governance quality can be exploited to measure and monitor aspects of legal, bureaucratic and administrative quality. Such a 'quick fix' approach to measuring governance quality is fraught with challenges. The current practice of measurement is still subject to the short country coverage of most available measures, issues of comparability and legitimacy, as well as methodological shortcomings. Second, we argue that, in the long run, measuring and monitoring governance quality may require reconceptualising 'good governance' and designing internationally shared measures that are routinely provided by national statistical offices (but, international groups should also continue to make their independent measures). Finally, we consider the different approaches to setting governance goals, arguing in favour of a combination of national target setting and minimum standard with continuous improvement. Abstract : Of particular significance are ongoing debates about whether good governance is good for development and/or, whether good enough governance is the best to which nations can aspire.